Uptake of fluorescent d- and l-glucose analogues, 2-NBDG and 2-NBDLG, into human osteosarcoma U2OS cells in a phloretin-inhibitable manner - Ogawa, Tetsuya (Hum Cell, 2021)
Mammalian cells take in d-glucose as an essential fuel as well as a carbon source. In contrast, l-glucose, the mirror image isomer of d-glucose, has been considered merely as a non-transportable/non-metabolizable control for d-glucose. We have shown that 2-[N-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxy-D-glucose (2-NBDG), a d-glucose analogue combining a fluorophore NBD at the C-2 position, is useful as a tracer for monitoring d-glucose uptake through glucose transporters (GLUTs) into mammalian cells. To more precisely evaluate the stereoselectivity of 2-NBDG uptake, we developed an l-glucose analogue 2-NBDLG, the mirror-image isomer of 2-NBDG. Interestingly, 2-NBDLG was taken up into mouse insulinoma MIN6 cells showing nuclear heterogeneity, a cytological feature of malignancy, while remaining MIN6 cells only exhibited a trace amount of 2-NBDLG uptake. The 2-NBDLG uptake into MIN6 cells was abolished by phloretin, but persisted under blockade of major mammalian glucose transporters. Unfortunately, however, no such uptake could be detected in other tumor cell lines. Here we demonstrate that human osteosarcoma U2OS cells take in 2-NBDLG in a phloretin-inhibitable manner. The uptake of 2-NBDG, and not that of 2-NBDLG, into U2OS cells was significantly inhibited by cytochalasin B, a potent GLUT inhibitor. Phloretin, but neither phlorizin, an inhibitor of sodium-glucose cotransporter (SGLT), nor a large amount of d/l-glucose, blocked the 2-NBDLG uptake. These results suggest that a phloretin-inhibitable, non-GLUT/non-SGLT, possibly non-transporter-mediated yet unidentified mechanism participates in the uptake of the fluorescent l-glucose analogue in two very different tumor cells, the mouse insulinoma and the human osteosarcoma cells. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13577-020-00483-y.